2018
DOI: 10.3390/resources7040080
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Social Pressures in Mining. Results from a Sustainability Hotspots Screening

Abstract: In recent years, increased interest and actions have been taken to better understand, and mitigate, sustainability impacts of mining activities, by both industry and policy. The present work reports on a sustainability hotspots screening performed for the EU Horizon 2020 “Integrated Mineral Technologies for More Sustainable Raw Material Supply” (ITERAMS) project, which foresees a more efficient water recycling, tailings valorization, and minimization of environmental footprint. The focus of this paper is on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Therefore, this shows that the DW company performs relatively better than the other companies of the Zero Brine system. These results are in agreement with Di Noi et al [79] who concluded that workers and local community were mainly affected due to mining operations. Due to regulation, workers and local community are greatly affected similarly to what our results show about Russia and the Russian mining company.…”
Section: Prevention and Mitigation Of Conflictssupporting
confidence: 93%
“…Therefore, this shows that the DW company performs relatively better than the other companies of the Zero Brine system. These results are in agreement with Di Noi et al [79] who concluded that workers and local community were mainly affected due to mining operations. Due to regulation, workers and local community are greatly affected similarly to what our results show about Russia and the Russian mining company.…”
Section: Prevention and Mitigation Of Conflictssupporting
confidence: 93%
“…In other words, a shift from an unsustainable to a sustainable society requires radical structural changes, providing a "Deep Transition" [21] through the series of connected transitions to sustainable development in many socio-technical systems [22][23][24][25]. According to the Human and Nature Dynamics (HANDY) model, avoiding civilizational collapse requires major policy changes, including a significant decrease in the depletion of nature and a major reduction in inequality [26], which in turn require appropriate strategic social, economic, and environmental innovation.…”
Section: Focusing On Long-term Rationalitymentioning
confidence: 99%
“…It implies not only SD triple dimensions but also outlines the necessity of considering long-term SD effects (including effects of innovation activities) [12] (pp. [19][20][21][22][23]. Strategic technological innovation activities are, thus, crucial for solving critical resource and environmental problems plaguing today's society, including the development of environmentally clean, safe, and efficient sources of energy, and waste-free and zero-emission production technologies [28][29][30][31].…”
Section: Focusing On Long-term Rationalitymentioning
confidence: 99%
“…The German mining sector has always played a major role in the German economy, and the gross electricity generation in Germany in 2016 accounted for 40% by coal-fired power plants [66]. Coal is extracted in open pit mines that are wide and shallow, as confirmed by the mining volume per unit of area (8.45 m 3 /m 2 ), and many environmental and social impacts are related to the huge demand of coal in Germany, while mining and landfilling activities find fierce opposition in local communities [67][68][69]. The consistent amount of materials transferred to and from mining and landfilling sites causes large-scale anthropogenic disturbance to the natural ecosystem, local communities, and alter the natural topography.…”
Section: Geographical Changes Of the German Landscapementioning
confidence: 99%